Antecedents of Counterproductive Behavior at Work: A General Perspective. - Marcus, Bernd; Schuler, Heinz (Journal of Applied Psychology, 2004)
Counterproductive work behaviors have predominantly been investigated at relatively narrow levels, with the focus limited to subsets of the behavioral domain as well as to specific explanatory approaches. This study took a broader perspective with respect to both dependent and independent variables. A sample of German employees from 2 organizations reported on their levels of general counterproductive behavior (GCB). In predicting GCB, M. R. Gottfredson and T. Hirschi's (1990) theory of self-control as a general explanation for deviant acts was tested and compared with several alternative approaches. Results from simple and moderated hierarchical multiple regression analyses involving 24 predictors of GCB strongly support hypotheses derived from self-control theory. Little support is found for any effects on individual differences in GCB beyond the direct and conditional impact of internal control.